Analisis Kualitas Jasa Pelayanan Bagian Administrasi Akademik & Kemahasiswaan (Baak) Di Universitas Panca Bhakti Pontianak Provinsi Kalimantan Barat - Ery Niswan; Semmy Faldo (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2021)
Research is entitled "Analysis of Service Quality of Academic Administration & Student Departement (BAAK) at Panca Bhakti University Pontianak, West Borneo". The efforts of higher education institutions are to facilitate the community to pursue higher education through integrated services in which there are dimensions of service quality in the form of reliability, tangibles, responsiveness, assurance, and empathy. The research method used in this research is a survey method, with respondents who are active students of Panca Bhakti University in four faculties as many as 80 respondents. The data analysis technique used is descriptive analysis technique. From the research that has been conducted at Panca Bhakti University, the results of the analysis of performance appraisals and the assessment of expectations from the dimensions of service quality in the form of reliability, tangibles, responsiveness, assurance, and empathy were obtained for each dimension of the number 0.99 (Q) ≤ 1, which means that overall the quality of service can be concluded as close to "good".